A single-center cost analysis assessing a change in vasopressin formulation. (4th April 2021) - Kelly, Courtney E; Miller, Christopher; Darko, William; Cwikla, Greg; Mogle, Bryan; Featherly, Julianna; Marcinak, Rebecca; Probst, Luke A; Seabury, Robert
Abstract: Purpose: Cost savings achieved at an academic medical center by reformulating the institution's standard vasopressin infusions to reduce waste are described. Summary: After a retrospective review of vasopressin utilization over a 4-month period revealed that only approximately 40% of dispensed vasopressin units were actually administered to patients, pharmacy leaders determined that the institution's standard vasopressin concentration for continuous infusions (100 units in 100 mL of sodium chloride 0.9% injection) was resulting in substantial waste, as many infusion preparations were not needed within the 18- to 24-hour expiration window. A concentration of 20 units/100 mL was adopted as the new standard formulation for vasopressin continuous infusions, with use of alternative concentrations allowed on a restricted basis. A pre-post study to assess the impact of the formulation change indicated a 38.7% decrease in vasopressin utilization (from 21, 900 to 8, 480 units) relative to utilization in a retrospective sample of patients who received vasopressin infusions prior to the formulation change. This reduced utilization equated to a cost decrease of 55, 656.20 (as calculated on the basis of 2017 cost estimates) or 77, 214.23 (as calculated on the basis of 2019 cost estimates) for the time period collected. It was estimated that the new formulations could yield annual cost savings ranging from 222, 625 to 308, 857. Conclusion: To our knowledge, this is the first description of cost savings following a change in formulation of vasopressin for continuous infusions. Other institutions could consider employing a similar approach in addition to the previously reported cost-saving interventions, such as lower vasopressin starting doses and vasopressin restriction policies.